EFEKTIFITAS MODEL REGRESI LINIER BERGANDA DAN GEOGRAPHICALLY WEIGHTED REGRESSION (GWR) DALAM MEMODELKAN NILAI TANAH PADA KAWASAN INDUSTRI SEDAYU - Pramudita, Indra; Djojomartono, Prijono Nugroho (Jurnal Spasial, 2024)
The Sedayu industrial area located in Argodadi Village, has been designated as a district's strategic economic area. This has an impact on land of Argodadi Village in terms of land tenure, land use and land value. To avoid land speculators causing land values to soar, it is necessary to have plot-based land value information. Land value modeling can be carried out using Ordinary Least Square (OLS) and Geographically Weighted Regression (GWR) methods. Based on the analysis of the model compatibility test, the coefficient of determination, spatial heterogeneity, and the spatial autocorrelation index, it is found that GWR is more effectively used than OLS. GWR produces 9988 models which equal the number of analyzed fields. The results of the prediction to the industrial estate land values are displayed in a map of the value of land parcels which are grouped into 71 classes, namely in the class range of 31 to 103.